2012
DOI: 10.1038/hr.2012.90
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide linkage and association scans for pulse pressure in Chinese twins

Abstract: Elevated pulse pressure (PP) is associated with cardiovascular disorders and mortality in various populations. The genetic influence on PP has been confirmed by heritability estimates using related individuals. Recently, efforts have been made by mapping genes that are linked to the phenotype. We report the results of our gene mapping studies conducted in the Chinese population in mainland China. The genome-wide linkage and association scans were carried out on 63 middle-aged dizygotic twin pairs using high-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 38 publications
0
8
1
1
Order By: Relevance
“…5, 6, 8, 9, 39-41 In this study, in contrast with the rare variant result, we did not identify novel common variants that significantly influenced BP levels. We showed consistent results for four common BP SNPs, located in ULK4 , SLC39A8 , HFE , SH2B3 , that were reported by the ICBP consortium 6 and were captured in our whole exome sequencing.…”
Section: Discussioncontrasting
confidence: 71%
“…5, 6, 8, 9, 39-41 In this study, in contrast with the rare variant result, we did not identify novel common variants that significantly influenced BP levels. We showed consistent results for four common BP SNPs, located in ULK4 , SLC39A8 , HFE , SH2B3 , that were reported by the ICBP consortium 6 and were captured in our whole exome sequencing.…”
Section: Discussioncontrasting
confidence: 71%
“…We found that the brown module was strongly overrepresented with genes associated with genetic risk for disease ( P  = 6.3 × 10 −14 , Odds Ratio = 2[1.7–2.4]), as were the brown hub genes specifically ( P  = 6.1 × 10 −6 , Odds Ratio = 3.6[2.0–6.4]). These hubs include genes associated with body-mass index and obesity related traits ( GNB1 , PPP1CB , RCAN2 , RSBN1 , PSD3 , TOMM20 ) 34, 35 ; anorexia nervosa ( PPP3CA ) 36 ; bipolar disorder ( MARCKS , BASP-1 ) 37, 38 ; and schizophrenia ( GPM6A ) 39 . Since the reward circuitry is central to both addictive and feeding behaviors and several hub genes were associated with BMI and obesity, we specifically tested if BMI and obesity genes were enriched in the brown module.…”
Section: Resultsmentioning
confidence: 99%
“…Intriguingly, alleles conferring migraine susceptibility were also associated with risk for CHD suggesting a common pathophysiology. The distal haplotype block of PHACTR1 also contains hits in the GWAS catalogue (www.genome.gov/gwastudies; accessed May 2013; [21]), originating from a 100k GWAS for femoral neck width in females of the Framingham Heart Study [43] and a linkage study for pulse pressure in 63 Chinese sib-pairs [44] (Fig. 2b).…”
Section: Chr6p241 (Phactr1): Frequently Replicated But Poorly Undersmentioning
confidence: 99%